Analysis of Diana Baumrind's Parenting Style on Early Childhood Development - M. Fadlillah; Syifa Fauziah (STAI Hubbulwathan Duri, 2022)
One of the most influential parenting figures in the world is Diana Baumrind. His studies on parenting are widely used as references by some scientists in various countries. On the other hand, the parenting theory he found was often associated with children's academic achievement. The purpose of this study was to describe and analyze Diana Baumrind's parenting style and its relationship to early childhood cognitive development. The research method used is descriptive qualitative with a literature study approach. The main data of this research is a scientific article from Diana Baumrind which contains parenting styles. The results showed that there are four parenting styles of Diana Baumrind that have an influence on children's cognitive development, namely authoritative, authoritarian, permissive, and neglecting. Each style has a different effect, both positive and negative. Parents can choose and determine the parenting style according to the needs and characteristics of the child's development. In short, every parent's support and motivation in parenting will determine the child's life in the future.